2008
DOI: 10.1002/jbm.a.31809
|View full text |Cite
|
Sign up to set email alerts
|

The role of calcium gluconate in electrochemical activation of titanium for biomimetic coating of calcium phosphate

Abstract: Supersaturation of calcium and phosphate in the bath solution and activation of the metal substrate is essential for effective biomimetic growth of apatite on orthopedic implants. In this work, bioactivation of titanium surface was achieved by electrodeposition of a thin layer of calcium phosphate followed by an alkaline treatment to obtain pure hydroxyapatite crystals. The influence of calcium gluconate in the electrolyte solution was evaluated and optimized. Adhesive strength, thickness, structural, and surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Thus, much effort has been devoted to apply bioactive and osteoconductive nano HA materials as coatings on implant materials for orthopedic applications (Webster et al 2002;Choi et al 2004;Bigi et al 2005;Sato et al 2005Sato et al , 2006Sato et al , 2007Balasundaram et al 2006;Evis et al 2006;Narayanan et al 2008;Teng et al 2008;Ciobanu et al 2007;Shibli and Mathai 2008). For instance, recently it has been reported that enhanced cell functions were observed on titanium coated with nano HA by an electrochemical method (Narayanan et al 2008).…”
Section: Osteoblast Adhesionmentioning
confidence: 99%
“…Thus, much effort has been devoted to apply bioactive and osteoconductive nano HA materials as coatings on implant materials for orthopedic applications (Webster et al 2002;Choi et al 2004;Bigi et al 2005;Sato et al 2005Sato et al , 2006Sato et al , 2007Balasundaram et al 2006;Evis et al 2006;Narayanan et al 2008;Teng et al 2008;Ciobanu et al 2007;Shibli and Mathai 2008). For instance, recently it has been reported that enhanced cell functions were observed on titanium coated with nano HA by an electrochemical method (Narayanan et al 2008).…”
Section: Osteoblast Adhesionmentioning
confidence: 99%
“…Moreover, this method ensures the sol's homogeneity, the possibility to regulate polycondensate molecules, a large number of metalorganic and inorganic metal salt compounds, used as precursors, as well as the possibility to obtain multiingredient coatings of high purity on different bases. 7,8 Another important factor affecting the final quality of the products that come into contact with blood is the proper resistance of the modified surface to medical sterilisation. Presently, cardiovascular implants are usually sterilised with ethylene oxide (EO) and with pressurisedwater steam in an autoclave.…”
Section: Introductionmentioning
confidence: 99%
“…Many researches have been dedicated to preparing Ti/ HA composite materials in a biomimetic route recently. The so called biomimetic coating technique is to induce the deposition of apatite in simulated body fluid (SBF), 5 with ion concentrations nearly equal to those of human extracellular fluid. It is apparent that this method can be readily adapted to synthesising Ti/HA composite materials since it does not require complex equipment, the objects to be coated can be large or irregularly shaped.…”
Section: Introductionmentioning
confidence: 99%